Visual decision support for business ecosystem analysis. (15th December 2016) - Basole, Rahul C.; Huhtamäki, Jukka; Still, Kaisa; Russell, Martha G.
Highlights: Comparative evaluation of the effectiveness of three ecosystem visualization methods. Extend cognitive fit theory to examine impact of ecosystem complexity and task type. Ecosystem complexity significantly influences decision performance. Contribute to our understanding of visual business ecosystem intelligence tools. Abstract: This study comparatively evaluates the effectiveness of three visualization methods (list, matrix, network) and the influence of data complexity, task type, and user characteristics on decision performance in the context of business ecosystem analysis. We pursue this objective using an exploratory study with 14 prototypical users (e.g. executives, analysts, investors, and policy makers). The results show that in low complexity contexts, decision performance between visual representations differ but not substantially. In high complexity contexts, however, decision performance suffers significantly if visual representations are not appropriately matched to task types. Our study makes several theoretical and practical contributions. Theoretically, we extend cognitive fit theory by investigating the impact of business ecosystem task type and complexity. Managerially, our study contributes to the relatively underexplored, but emerging area of the design of business ecosystem intelligence tools and presentation of business ecosystem data for the purpose of decision making. We conclude with future research opportunities.